MODIFICACIÓN DEL DISEÑO DE UNA BOMBA CENTRIFUGA PARA REDUCCIÓN DE VIBRACIONES CAUSADAS POR TURBULENCIAS (2021)
The operation of turbomachines as supercharging elements is based under a high speed regime causing vibrations that later, when not controlled, tend to generate failures, passing through the bearings to the casing. Among these turbomachines are centrifugal pumps that will be the object of analysis for this document, with the aim of reducing vibrations caused by the turbulent flow that passes through it and that could significantly decrease their performance causing failures or accidents. Through the application of the finite element method, it is sought to modify the geometry to reduce turbulence and consequently vibrations. The results obtained made it possible to measure the displacement caused in the support bearings and thus how they can affect the performance curve of the pump. On the other hand, it was observed that none of the modifications made allows a significant change in the performance of the pump and in the reduction of vibrations.